2021
DOI: 10.1111/jfpe.13876
|View full text |Cite
|
Sign up to set email alerts
|

Design, development, and drying kinetics of infrared‐assisted hot air dryer for turmeric slices

Abstract: An infrared-assisted hot air dryer was designed and developed for turmeric slices. The dryer has been developed using an infrared heating source, heating coils, and blower.The total power required for the infrared drying and hot air drying was 2.25 kW and 36.35 kWh, respectively, with a blower capacity of 6.06 m 3 /min. An infrared drying (IRD), hot air drying (HAD), and infrared-assisted hot air drying (IRHAD) were used to dry turmeric slices (5 mm thickness) at different drying temperatures 50 C, 60 C, and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
4
19
0
Order By: Relevance
“…The curcumin, oleoresin, starch, and color ( L , a , b value) of 4.92%, 16.5%, 58.09%, and 59.87 ( L ), 28.43 ( a ), 74.21 ( b ) was found higher at 9 rpm, 50°C air temperature, and 3 m/s air velocity. Similar results were reported for infrared assisted hot air drying of turmeric slices (Jeevarathinam et al, 2021a, 2021b), blanching of turmeric (Farzana et al, 2018), and solar and convection oven drying of turmeric (Raza et al, 2018). The statistical analysis showed a significant difference ( p ≤ 0.01) between the speed of drum, air temperature and velocity for all quality parameter (Table 3).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The curcumin, oleoresin, starch, and color ( L , a , b value) of 4.92%, 16.5%, 58.09%, and 59.87 ( L ), 28.43 ( a ), 74.21 ( b ) was found higher at 9 rpm, 50°C air temperature, and 3 m/s air velocity. Similar results were reported for infrared assisted hot air drying of turmeric slices (Jeevarathinam et al, 2021a, 2021b), blanching of turmeric (Farzana et al, 2018), and solar and convection oven drying of turmeric (Raza et al, 2018). The statistical analysis showed a significant difference ( p ≤ 0.01) between the speed of drum, air temperature and velocity for all quality parameter (Table 3).…”
Section: Resultssupporting
confidence: 80%
“…The contour plots were compared between 60° and 70°C of 9 rpm (Figure 6c) and 6 rpm (Figure 7c) at 3 m/s. The contour plots showed that the higher moisture removal ratio was found at 70°C because of rapid moisture evaporation (Falade, Olurin, Ike, & Aworh, 2007; Jeevarathinam et al, 2021b). At 9 rpm and 3 m/s, 70°C (Figure 6b,c) showed higher drying rate and moisture removal compared to 60°C and for both temperatures the predicted and observed values were on par (Figure 6a,c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the drying time of the products was decreased at higher inlet temperatures, so the longest and shortest process times were related to drying at 40 and 60 • C, respectively. Increasing the temperature of the product surface led to an increase in mobility of water molecules and as a result easier migration of these molecules from the internal parts to the product surface [54]. Increasing the temperature on the one hand increased the moisture absorption capacity of the air due to increasing the temperature difference between the air and the product and on the other hand caused faster heating of the product and better evaporation of water from it and ultimately reduced drying time [55].…”
Section: Drying Kineticsmentioning
confidence: 99%